2020
DOI: 10.1088/2631-8695/ab8957
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation histotripsy at the surface of soft material using the dual-frequency excitation

Yufeng Zhou,
Yisheng Lei

Abstract: Cavitation histotripsy has been applied for the disintegration at the interface of soft tissue and fluid in a well-controlled manner. The dual-frequency excitation was proposed and evaluated in this study. The acoustic field generated by the dual-frequency (1.09+1.11 MHZ) excitation and associated bubble dynamics at the focus was simulated using Khokhlov-Zabolotskaya-Kuznetsov equation and Gilmore model, respectively, and compared with those by the single-frequency (1.1 MHz) excitation at the same power. Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…It should be noted that the period number of lower frequency is used for the dual-frequency case, similar to the previous study (Wang et al 2021). Actually, the amplitude of dualfrequency ultrasound is modulated by the two single-frequency components (Yeh et al 2009, Guédra et al 2017, Law and Zhou 2018, Suo et al 2018, Zhou and Lei 2020, thus the dual-frequency driving is still periodic and its period can be calculated as the method described in the previous study (Hegedűs et al 2020). In our simulations, the calculations were performed during five periods of the dual-frequency ultrasound.…”
Section: Comparation Of Bubble Dynamics Under Single-and Dual-frequen...mentioning
confidence: 92%
See 1 more Smart Citation
“…It should be noted that the period number of lower frequency is used for the dual-frequency case, similar to the previous study (Wang et al 2021). Actually, the amplitude of dualfrequency ultrasound is modulated by the two single-frequency components (Yeh et al 2009, Guédra et al 2017, Law and Zhou 2018, Suo et al 2018, Zhou and Lei 2020, thus the dual-frequency driving is still periodic and its period can be calculated as the method described in the previous study (Hegedűs et al 2020). In our simulations, the calculations were performed during five periods of the dual-frequency ultrasound.…”
Section: Comparation Of Bubble Dynamics Under Single-and Dual-frequen...mentioning
confidence: 92%
“…In addition to introducing encapsulated microbubbles, dual-or multiple-frequency ultrasound has recently been utilized to reduce cavitation thresholds and increase cavitation effects, as compared with the conventional single-frequency ultrasonic cavitation. Experimental investigations have confirmed that the dual-frequency excitation could significantly reduce the inertial cavitation threshold and improve the efficiencies of thrombolysis (Suo et al 2015, histotripsy (Law andLei 2020), sonodynamic therapy (Alamolhoda et al 2012, Ninomiya et al 2014, and so on. Moreover, some numerical studies have also attempted to elucidate the potential mechanisms of the enhanced bubble cavitation by dual-or multiple-frequency excitation.…”
Section: Introductionmentioning
confidence: 92%
“…Researchers have already conducted some studies on the nonlinear effects of dual-frequency ultrasound. In these studies, only specific pairs of dual-frequency combination were investigated (e.g.,3.16 MHz + 3.20 MHz used in Reference [28] and 1.09 MHz + 1.11 MHz used in Reference [29] ) and it is necessary to extend the frequency range to have a comprehensive understanding of characteristics of dual-frequency ultrasound. Moreover, the effects of nonlinearity on the temperature raise caused by ultrasound which play an important role in the biomedical ultrasound applications should be taken into consideration as well.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effects of nonlinearity on the temperature raise caused by ultrasound which play an important role in the biomedical ultrasound applications should be taken into consideration as well. Added to that, KZK equation was commonly used to model the nonlinear propagation of dual-frequency ultrasound wave nowadays [28] , [29] , [30] , which was a simplification based on the parabolic approximation. The generalized Westervelt equation in the time domain will be better to simulate the acoustic field more accurately especially when severe waveform distortion is produced [31] .…”
Section: Introductionmentioning
confidence: 99%
“…Our interest on the possibility that cavitation bubbles may excite shear waves is motivated by the rather common occurrence of bubble nucleation in a variety of medical procedures such as high intensity focused ultrasound (HIFU), 12,13 histotripsy, 14,15 laser lithotripsy 16,17 and thermal ablation of tumours, 18,19 to name a few. Also, cavitation has been reported to occur within the brain following the impact of the skull, 20 as well as in synovial fluid during joint cracking.…”
Section: Introductionmentioning
confidence: 99%